Makna Upacara Adat Reba (Syukuran Atas Hasil Panen) Bagi Masyarakat Bajawa Kabupaten Ngada Provinsi Nusa Tenggara Timur: Indonesia - Vercelli Elisabeth Fono; Omiano Sabu; Jeff Wilfred Mesah (Universitas Persatuan Guru 1945 NTT, 2026)
The Meaning of the Reba Traditional Ceremony (Thanksgiving for the Harvest) for the Bajawa Community, Ngada Regency, East Nusa Tenggara Province.